GOVERNANCE & SHARIA ISSUES IN INVESTMENT ACCOUNT - Yaseer Taufik Syamlan (Airlangga International Journal of Islamic Economics and Finance, 2018)
Corporate Governance and Sharia Governance has been the main key of the existence of Islamic finance industry. Recently there are some issues which related to governance which are sharia arbitrage, Investment account holder treatment and the need of professional ethic for Sharia Supervisory Board member. These three issues if in the future can be managed properly will take the industry forward. But, the practice of good corporate and sharia governance still based on the Islamic Finance discretion. Since the Islamic finance industry still growing, the carefulness in conducting all transaction with a spirit of good corporate and sharia governance will be benefit to the development of industry in the future.